Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor; Raum- und Verkehrsinfrastrukturentwicklung in Europa: Das Beispiel Orient/East-Med Corridor - Bernd Scholl; Ana Perić; Mathias Niedermaier (Verlag der ARL - Akademie für Raumforschung und Landesplanung, 2019)
The Orient/East-Med Corridor is a key north-south transport corridor for Europe. Over its length of more than 2,500 km, it connects the seaports of northern Germany with the Danube ports and Greek seaports. Seven capitals of EU member states are directly interlinked by the Corridor. At present however, it has genuine shortcomings in several aspects. The international working group "Spatial and Transport Development in European Corridors: Example Corridor 22, Hamburg-Athens" (2015-2018) trace the conditions for large scale, corridor oriented spatial and transport development in Europe and in particular along the Orient/East-Med Corridor. The contributions in the anthology also focus on the importance of transnational initiatives in Europe and on territorial effects of transport policies. These topics are illustrated by analyses of current transport initiatives and urban developments at the most important nodes along the Corridor, so called Hot-Spots. During the work process, the authors asked themselves, if and how a strategy for the Corridor can take effect for an integrated spatial and transport development between Hamburg and Athens. The common answer is clear: A strategy for the Orient/East-Med Corridor allows the organization of a more balanced flow of goods throughout Europe in the long run. In the southeast section, enormous land reserves in the close vicinity of railway stations can be activated for urban development. Strengthening the Corridor's infrastructure thus has a huge potential to trigger spatial development and ultimately contribute to territorial and social cohesion throughout Europe. – – Der Orient/East-Med Corridor ist ein für Europa wichtiger Nord-Süd-Verkehrskorridor. Auf einer Länge von mehr als 2.500 km verbindet er die norddeutschen Überseehäfen mit den Häfen der Donau und der griechischen Küstenstädte. Sieben Hauptstädte der EU-Mitgliedstaaten sind durch den Orient/East-Med Corridor direkt miteinander verbunden. Derzeit steht die Infrastrukturentwicklung des Corridors jedoch vor erheblichen Herausforderungen. Der internationale Arbeitskreis "Spatial and Transport Development in European Corridors: Example Corridor 22, Hamburg-Athens" (2015-2018) zeigt die Bedingungen auf, die für eine korridororientierte Raum- und Verkehrsentwicklung in Europa und insbesondere am Orient/East-Med Corridor bestehen. Ein besonderer Fokus wird auf die Funktionsweise grenzüberschreitender Zusammenarbeit sowie auf die räumliche Wirkung von Verkehrspolitik gelegt. Durch Analyse der aktuellen Ansätze aus der Verkehrsplanung und Stadtentwicklung werden diese Themen an den bedeutendsten Knotenpunkten des Corridors anschaulich untersucht. Während des Arbeitsprozesses stellten sich die Autoren die Frage, ob und wie eine Strategie für den Korridor langfristig hin zu einer abgestimmten Entwicklung von Raum und Verkehr führen kann. Die gemeinsame Antwort ist: Eine Strategie für den Orient/East-Med Corridor ermöglicht eine ausgewogenere Verteilung der Güterströme durch Europa. Im Südosten Europas können bspw. umfangreiche Flächenreserven in unmittelbarer Nähe von Bahnhöfen für die Stadtentwicklung genutzt werden. Eine Stärkung der Infrastruktur des europäischen Corridors hat somit ein enormes Potenzial, die Raumentwicklung anzuregen und letztendlich zum territorialen und sozialen Zusammenhalt in ganz Europa beizutragen.
urn:nbn:de:0156-09529; https://econpapers.repec.org/RePEc:zbw:arlfba:213376; https://econpapers.repec.org/RePEc:zbw:arlfba:213385; https://econpapers.repec.org/RePEc:zbw:arlfba:213386; https://econpapers.repec.org/RePEc:zbw:arlfba:213377; https://econpapers.repec.org/RePEc:zbw:arlfba:213372; https://econpapers.repec.org/RePEc:zbw:arlfba:213374; https://econpapers.repec.org/RePEc:zbw:arlfba:213381; https://econpapers.repec.org/RePEc:zbw:arlfba:213373; https://econpapers.repec.org/RePEc:zbw:arlfba:213378; https://econpapers.repec.org/RePEc:zbw:arlfba:213375; https://econpapers.repec.org/RePEc:zbw:arlfba:213379; https://econpapers.repec.org/RePEc:zbw:arlfba:213371; https://econpapers.repec.org/RePEc:zbw:arlfba:213387; https://econpapers.repec.org/RePEc:zbw:arlfba:213382; https://econpapers.repec.org/RePEc:zbw:arlfba:213380; https://econpapers.repec.org/RePEc:zbw:arlfba:213384; https://econpapers.repec.org/RePEc:zbw:arlfba:213383
Keywords: 710; Orient/East-Med Corridor; integrated spatial and transport development; territorialeffects of transport policies; transnational initiatives in Europe; corridor development strategy; integrierte Raum- und Verkehrsentwicklung; räumlicheWirkung von Verkehrspolitik; grenzüberschreitende Initiativen in Europa; Corridor-Entwicklungsstrategie